2019
DOI: 10.1007/s10661-018-7174-5
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of the replicability of a standard and modified sanitary risk protocol for groundwater sources in Greater Accra

Abstract: Sanitary risk inspection, the systematic observation of contamination hazards, is often used to manage safety of water sources such as wells and boreholes. However, the replicability of sanitary risk inspections undertaken by different observers has not been studied. This study aimed to assess the replicability of sanitary risk inspections by two different observers in urban and peri-urban neighbourhoods of Greater Accra, Ghana. Two observers independently used a standard protocol to record contamination hazar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 28 publications
0
8
1
2
Order By: Relevance
“…Our findings from rural Kenya indicate much lower agreement between observers recording contamination hazards than we identified in our earlier study in Greater Accra, Ghana (Yentumi et al 2018). There are several reasons why this might be the case.…”
Section: Discussioncontrasting
confidence: 83%
See 3 more Smart Citations
“…Our findings from rural Kenya indicate much lower agreement between observers recording contamination hazards than we identified in our earlier study in Greater Accra, Ghana (Yentumi et al 2018). There are several reasons why this might be the case.…”
Section: Discussioncontrasting
confidence: 83%
“…If sanitary risk inspection protocols are to form a robust basis for water source remediation or comparing the relative safety of sources in different areas via water source surveys, then observations need to be consistent across observers. We recently conducted a small-scale study of inter-observer agreement of sanitary risk observations at groundwater sources in Greater Accra, Ghana, finding high agreement between two observers (Yentumi et al 2018). To avoid personal safety risks from lone working, both observers visited water sources in Greater Accra at the same time, though they observed and recorded hazards separately.…”
Section: Jmpmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies of risk perception within industries such as aviation [24][25][26] have shown diverse trends in risk perception between experts, professionals and novices. Though the importance of both capacity building within the wider water sector [27] and, more specifically, suitable training prior to undertaking an SI is acknowledged in the literature [6,28], there is limited published data regarding the consistency of SI inter-inspector answer agreement [29,30]. However, such consistency is vital to allow for potential comparability of SI outputs.…”
Section: Introductionmentioning
confidence: 99%